A competência legislativa municipal e a permissão de utilização das queimadas controladas nos Campos de Cima da Serra à luz da função social da propriedade - Milhoranza, Mariângela Guerreiro (2015)
Municipal legislative jurisdiction to enact statutes allowing controlled burning in a region known as “Campos de Cima da Serra” has been examined as the subject of this research. It has been sought to demonstrate that the controlled burning, which is as a century old practice in “Campos de Cima da Serra”, had been a beneficial and not harmful alternative for the said region, and within the scope of the social function of property. The First Chapter has addressed the issue of the Social Environmental State of Law and the protection of the environment as a fundamental right based primarily upon solidarity. Taking environmental rights as fundamental rights, the interaction between human beings and their “place of gathering” has been analyzed, and environmental catastrophes, which have been caused by a degraded (ill conceived) anthropic interaction, have been studied in the First Chapter. Geographical, historical and biological traits of “Campos de Cima da Serra” have been studied in Chapter Two, which has allowed a deeper analysis of impacts on fauna and flora caused by controlled burning in the region subject of this research. Chapter Three has addressed some instructions to enact municipal legislation which will grant (landonwers and the State) permission to perform controlled burning in “Campos de Cima da Serra”. In the final section of the research it has been sought to clarify some of the controversies which had been addressed throughout the study.